2010
DOI: 10.1371/journal.ppat.1000957
|View full text |Cite
|
Sign up to set email alerts
|

EspA Acts as a Critical Mediator of ESX1-Dependent Virulence in Mycobacterium tuberculosis by Affecting Bacterial Cell Wall Integrity

Abstract: Mycobacterium tuberculosis (Mtb) requires the ESX1 specialized protein secretion system for virulence, for triggering cytosolic immune surveillance pathways, and for priming an optimal CD8+ T cell response. This suggests that ESX1 might act primarily by destabilizing the phagosomal membrane that surrounds the bacterium. However, identifying the primary function of the ESX1 system has been difficult because deletion of any substrate inhibits the secretion of all known substrates, thereby abolishing all ESX1 act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
119
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(125 citation statements)
references
References 54 publications
4
119
0
1
Order By: Relevance
“…EspR regulates multiple genes associated with the synthesis of cell-wall lipids, including phthiocerol dimycocerosate, phenol glycolipid and mycolic acid (Blasco et al, 2012), and the ESX-1 system itself is important for the stability of the cell wall (Garces et al, 2010). Notably, both MprAB and PhoPR are also associated with regulation of the response to cell-wall damage and/or regulation of lipid synthesis (He et al, 2006;Walters et al, 2006), and we identified several genes that are shared by the EspR and PhoP regulons (Walters et al, 2006).…”
Section: Discussionmentioning
confidence: 89%
“…EspR regulates multiple genes associated with the synthesis of cell-wall lipids, including phthiocerol dimycocerosate, phenol glycolipid and mycolic acid (Blasco et al, 2012), and the ESX-1 system itself is important for the stability of the cell wall (Garces et al, 2010). Notably, both MprAB and PhoPR are also associated with regulation of the response to cell-wall damage and/or regulation of lipid synthesis (He et al, 2006;Walters et al, 2006), and we identified several genes that are shared by the EspR and PhoP regulons (Walters et al, 2006).…”
Section: Discussionmentioning
confidence: 89%
“…These findings augment the growing evidence that genes associated with the ESX-1 system contribute to the structure and integrity of the cell envelope. The espA operon is activated by thioridazine, an agent that damages the cell envelope (42), and an espA mutant was more susceptible to the detergent SDS (19). Furthermore, a recent paper reports that EspR regulates numerous genes involved in cell wall function and that it binds within the Rv0986-to-Rv0989c region (24), part of the in vivo genomic island containing mprAB (43).…”
Section: Discussionmentioning
confidence: 99%
“…The basis for this hypergrowth phenotype is unknown and is surprising in view of the decreased secretion of ESAT-6, EspA, and EspB, all virulence factors (5,11,19,53). However, Rv-D981 secretes low levels of these proteins, and perhaps this is sufficient for some functions.…”
Section: Fig 5 Secretion Of Esx-1 Substrate Proteins Is Dysregulated mentioning
confidence: 99%
See 1 more Smart Citation
“…Because ESX-1 is a transport system lacking in BCG, lack of export of an ESX-1-dependent lipid synthase might account for the loss of substance A. However, ESX-1-deficient M. tuberculosis lacking either the espA gene (Rv3616c) or the entire RD1 locus (17), which are both necessary for ESX-1 function, produces substance A at normal levels (SI Appendix, Fig. S1C).…”
Section: Resultsmentioning
confidence: 99%